Elevation of plasma-soluble HLA-G in childhood nephrotic syndrome is associated with IgE. (January 2017) - Liu, Yanqing; Lai, Meimei; Lou, Yunyan; Han, Qiuyue; Yang, Qing; Chen, Minguang; Li, Jingbo; Wang, Huiyan; Yan, Weihua; Zheng, Xiaoqun
Background: Nephrotic syndrome is related to immune system dysfunction. Soluble human leukocyte antigen-G has been suggested to have an immunomodulatory role. Additionally, human leukocyte antigen-G expression may be influenced by the 14-base pair insertion/deletion polymorphism. However, this molecule has not been investigated in nephrotic syndrome. Methods: Fifty-five children with nephrotic syndrome were enrolled: 24 primary nephrotic syndrome patients and 31 recurrent nephrotic syndrome patients. A group of 120 healthy subjects were included as reference controls. Additionally, 22 patients in nephrotic syndrome remission after treatments were also included. Both nephrotic syndrome patients and healthy subjects were genotyped for the 14-base pair insertion/deletion polymorphism. Plasma soluble human leukocyte antigen-G concentrations and serum immunoglobulin concentrations were determined. Results: Nephrotic syndrome patients showed significantly higher levels of both soluble human leukocyte antigen-G and immunoglobulin E compared to normal controls. Nephrotic syndrome patients presented a higher frequency of the −14-base pair allele than did normal controls. Soluble human leukocyte antigen-G concentrations in remission patients were dramatically lower compared to in nephrotic syndrome patients. Moreover, soluble human leukocyte antigen-G and immunoglobulin E were moderately correlated in nephrotic syndrome patients. Conclusions: The present study demonstrated that plasma soluble human leukocyte antigen-G concentrations were significantly elevated and that a relationship between serum total immunoglobulin E in nephrotic syndrome patients and the human leukocyte antigen-G −14-base pair allele may be a risk factor for nephrotic syndrome. These findings suggest that soluble human leukocyte antigen-G may be used as a monitoring marker for nephrotic syndrome patients' condition.